Análisis técnico-económico del rediseño en el paso peatonal del Colegio Aguirre Abad - Alvarado Ampuero, Sebastián Andrés (2025)
This degree thesis develops a technical-economic analysis of the redesign of the pedestrian bridge located in front of the Aguirre Abad School in Guayaquil, an infrastructure that currently presents deficiencies in structural, functional and accessibility aspects. Through a diagnostic evaluation that included visual inspections, application of non-destructive tests, user surveys, and architectural data collection, pathologies were identified that compromise the safety, comfort, and usability of the structure, especially for the educational community that uses it on a daily basis. The research proposes a redesign that incorporates architectural, urban and structural improvements, following Ecuadorian and international technical standards such as AASHTO and NEC. The solutions proposed include: a wide platform with universal accessibility, incorporation of a stair lift system for people with reduced mobility, efficient lighting, optimization of the drainage system with galvalume downspouts and gutters, as well as the integration of covered modules that will function as kiosks to revitalize the public space and strengthen economic activity in the surrounding área From the structural point of view, dead and live loads were calculated considering the actual pedestrian capacity and the normative load of 4.1 kN/m², ensuring that the design complies with the required safety and resistance parameters. In addition, an economic analysis was performed to demonstrate the financial viability of the project. The proposed redesign not only improves the mobility and safety of users, but also contributes to urban sustainability, social inclusion and aesthetic integration with the architectural environment of the sector.